BEYOND ALTRUISTIC AND COMMERCIAL CONTRACT MOTHERHOOD: THE PROFESSIONAL MODEL. (16th April 2012) - VAN ZYL, LIEZL; WALKER, RUTH
ABSTRACT: It has become common to distinguish between altruistic and commercial contract motherhood (or 'surrogacy'). Altruistic arrangements are based on the 'gift relationship': a woman is motivated by altruism to have a baby for an infertile couple, who are free to reciprocate as they see fit. By contrast, in commercial arrangements both parties are motivated by personal gain to enter a legally enforceable agreement, which stipulates that the contract mother or 'surrogate' is to bear a child for the intending parents in exchange for a fee. She is required to undergo medical examinations and to refrain from behaviour that could harm the foetus. The intending parents are the child's legal parents from the outset. The parties to the contract can, but are not expected to, maintain contact after the transaction is completed. We argue that contract motherhood should not be organized according to the norms of the gift relationship, and that contract mothers should be compensated for their labour. However, we accept that there are good reasons for rejecting the commercial model as a suitable framework for contract pregnancy, and argue, instead, in favour of viewing it as a profession.